FAKTOR – FAKTOR YANG MEMPENGARUHI DEVIDEN PER SHARE PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BURSA EFEK INDONESIA (2009-2010) (Students' Journal of Accounting and Banking, 2013)
This study aims to test how much current ratio factor, debt to equity ratio, earning per share, total assets turn over, return on assets, firmsize effect on the devidend per share. Also to find out where the most dominant factor affecting the devidend per share. This research use of multiple regression analysis of 23 companies that purposive sampling taken at the Indonesian Stock Exchange through secondary data Indonesian Capital Market Directory. Observation period from 2009 to 2010. The results of Analyses were performed using multiple regression analysis. The research found that the variables in the model of research that is the only variable that affects earnings per share significantly to the dividend per share. Current ratio, debt to equity ratio, total asset turnover, return on assets, firmsize no significant effect on dividend per share.Keywords: Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share(EPS), Total assets Turn Over (TATO), Return On Assets (ROA), Firmsize, Dividen Per Share (DPS)